2020
DOI: 10.1111/imig.12703
|View full text |Cite
|
Sign up to set email alerts
|

Parental Health Outcomes of Children’s Migration: Experimental Evidence from Ethiopia

Abstract: This study uses experimental data from the United States Diversity-Visa (DV) lottery to explore the impact of migration of children on the sending parents' health, helping to overcome the selection bias issue that plagues similar studies. Based on the inverted U-shaped relationship between BMI and longevity, the study finds that the health prospects of senders with BMIs under 25 increase weakly with migration, decreasing for those in the overweight category. In families with more educated fathers, migration im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Researchers have studied the relationship between children's migration and leftbehind older parents' physical health (Lu 2012;Evandrou et al 2017), mental health (Song 2017;Wang et al 2017;Inoue et al 2019;Mergo 2020), quality of life (Liang and Wu 2014;Ye, Chen and Peng 2017) and overall well-being (Gassmann et al 2012;Silverstein, Cong and Li 2006). Generally, research on leftbehind parents' mental health has reported increased depression (Cheng et al 2015;Song 2017;Wang et al 2017;Zhai et al 2015), loneliness (Cheng et al 2015;Liu and Guo 2007;Wang et al 2017), anxiety (Wang et al 2013;Arenas and Yahirun 2010), and poorer cognitive ability (Zhai et al 2015) among older parents with migrant children.…”
Section: Mental Health Of Older Left-behind Parentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have studied the relationship between children's migration and leftbehind older parents' physical health (Lu 2012;Evandrou et al 2017), mental health (Song 2017;Wang et al 2017;Inoue et al 2019;Mergo 2020), quality of life (Liang and Wu 2014;Ye, Chen and Peng 2017) and overall well-being (Gassmann et al 2012;Silverstein, Cong and Li 2006). Generally, research on leftbehind parents' mental health has reported increased depression (Cheng et al 2015;Song 2017;Wang et al 2017;Zhai et al 2015), loneliness (Cheng et al 2015;Liu and Guo 2007;Wang et al 2017), anxiety (Wang et al 2013;Arenas and Yahirun 2010), and poorer cognitive ability (Zhai et al 2015) among older parents with migrant children.…”
Section: Mental Health Of Older Left-behind Parentsmentioning
confidence: 99%
“…Since the late 1980s, increased international economic migration in Nepal has resulted in the traditional, agriculture-based economy moving to a remittance-based economy (Kunwar 2015). According to Nepal's Department of Foreign Employment, 3.8 million permits to work abroad were issued between 1993 and 2014, with almost 14 percent of the total population receiving international work permits (Ministry of Labour and Employment Nepal 2016). Most labor migrants from Nepal are unskilled (70 percent) or semi-skilled (27 percent), with the majority unemployed (40 percent) or engaged in agriculture (30 percent), prior to departure (Nepal 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These emotional effects included sadness, longing, guilt, and worry ( 36 ). Migration imposes an emotional cost on those left behind, which adversely affects their emotional health ( 37 ). While migration remittances can compensate for the partial loss of the self-reported health and mental health of parents left behind, they do not do so for the deterioration of other health indicators ( 38 ).…”
Section: Introductionmentioning
confidence: 99%